2016
DOI: 10.1179/2042618613y.0000000047
|View full text |Cite
|
Sign up to set email alerts
|

The influence of home exercise programs for patients with non-specific or specific neck pain: a systematic review of the literature

Abstract: Study design: Systematic review of randomized controlled trials (RCT). Objectives: To examine the effects of a therapeutic home exercise program (HEP) for patients with neck pain (associated with whiplash, non-specific, or specific neck pain, with or without radiculopathy, or cervicogenic headache) on pain, function, and disability. Our secondary aim was to describe the design, dosage, and adherence of the prescribed HEPs. Background: Neck pain is a leading cause of disability that affects 22-70% of the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
1
15
0
3
Order By: Relevance
“…To the best of our knowledge, several previous meta-analyses have reported on exercise for treating neck pain or neck disorders, [3438] but there is no meta-analysis on the treatment of CR by exercise at present. As the first systematic review of exercise as an intervention measure for CR, the latest and high-level evidence-based results are obtained by synthesizing the results of multiple studies, although the GRADE level of evidence is low for 2 outcomes due to high heterogeneity and possible publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, several previous meta-analyses have reported on exercise for treating neck pain or neck disorders, [3438] but there is no meta-analysis on the treatment of CR by exercise at present. As the first systematic review of exercise as an intervention measure for CR, the latest and high-level evidence-based results are obtained by synthesizing the results of multiple studies, although the GRADE level of evidence is low for 2 outcomes due to high heterogeneity and possible publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that physical activity improves QoL in individuals with chronic pain or depression, especially in the physical and psychological domains. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The evidence supports the use of motor control exercises targeting the neck and the low back in combination with other conservative interventions to reduce pain and disability for patients suffering musculoskeletal impairments . In addition, in a recent systematic review, it is highlighted that motor control exercises to the neck as well as manual therapy techniques targeted to the neck and jaw could help alleviate pain and disability in subjects with TMD .…”
Section: Introductionmentioning
confidence: 88%